The purple coneflower’s (Echinacea purpurea L.) nutrient requirements investigation in a small plot trial - Lelesz, Éva Judit (Acta Agraria Debreceniensis, 2018)
During our research, we investigated the purple coneflower’s (Echinacea purpurea L.) drug yield and drying loss change with different fertilization settings in a small-plot trial. We measured the raw and dry drug yield, which we harvested in 2016 and in 2017, as well as the drying loss of these yields. Harvest and all other works were performed manually. We dried the harvested herba under prenumbra for three weeks. Based on the obtained data, every fertilization settings’ yield was less than that of the control plots in 2016. We measured the highest drying loss in relation to the N60P80K120 supply in this year. In 2017, we measured the highest yield data in the N75P100K150 fertilization setting. We made single-factor variance analysis to investigate the connection between the quantity of the raw, the dried herba, the drying loss and the different nutrient settings